Vα14iNKT cell Deficiency Prevents Acetaminophen-Induced Acute Liver Failure by Enhancing Hepatic Glutathione and Altering APAP Metabolism - Downs, Isaac (2012)
Acetaminophen (APAP) overdose is widely regarded as a major cause of acute liver failure in the United States. Intentional or accidental overdose of APAP in man or rodent elicits direct hepatocellular injury that is accompanied by hepatic depletion of the antioxidant, glutathione (GSH). In recent years, the innate immune response has also been shown to promote the development of APAP hepatotoxicity via indirect liver damage. In the present study, we demonstrate that Jα18(−/−) mice, which are selectively deficient in the innate immune T cell, Vα14iNKT cells, were resistant to APAP hepatotoxicity relative to WT mice as reflected by biochemical and histological liver injury markers. In parallel, improvement in the biochemical and histological parameters of liver injury in Jα18(−/−) mice was associated with a significant increase in hepatic levels of GSH, which detoxified APAP metabolites to attenuate hepatic oxidative stress, liver injury and necrosis. Notably, the protective effect of hepatic GSH during Vα14iNKT cells deficiency was demonstrated by its depletion in Jα18(−/−) mice using DL-buthionine-[S,R]-sulfoximine which exacerbated hepatic oxidative and nitrosative stress as well as liver necrosis and caused mice mortality. Extraordinarily, APAP metabolism in Jα18(−/−) mice was altered in favor of hepatic GSH conjugates and decreased glucuronide conjugates. In summary, we reveal a novel finding establishing a unique association between hepatic innate immunity and GSH levels in altering APAP metabolism to suppress liver injury and necrosis during Vα14iNKT cells deficiency in Jα18(−/−) mice.